The specifics of clotting and endogenic fibrinolysis in acute coronary syndrome patients - A. I. Kalinskaya; P. P. Savvinova; E. Yu. Vasilieva; A. V. Shpektor (Российский кардиологический журнал, 2018)
Aim. To assess the processes of clot formation in relation to endogenic fibrinolysis in patients with various types of acute coronary syndrome (ACS).Material and methods. To the study, 89 persons (40 males) included: 59 with ACS, 30 — control group. Among the ACS patients, 28 were ST-elevation (STEMI), 31 with non-ST-elevation ACS (NSTEACS). All participants were assessed for clotting formation parameters and thrombus lysis with rotational elastometry on ROTEM equipment (Germany) and “Hemacore” Thrombodynamics (Russia), before coronary arteriography.Results. Clot density and its size in 10 minutes were significantly higher in ACS comparing to control patients (2867 units vs 25084 units, p<0,001; 41,8 mm vs 36,4 mm, p<0,05, respectively). The time from onset of thrombus lysis was lower in ACS (79,4 min vs 69,3 min, p<0,05). The percent of lysis by the end of process registration was lower in ACS (20,1% vs 23,1%, p<0,05). Amplitude of clot formation in 20 minutes from the onset of clotting, as the maximum density of clot were significantly higher in NSTEACS comparing to STEMI (56,2 mm vs 49,7 mm, p=0,018; 59 mm vs 53,2 mm, p=0,011; respectively). Thrombus lysis was slower in NSTEACS patients comparing to STEMI (62,26 min vs 45,5 min, p=0,02).Conclusion. With the measurement in vitro, the process of clotting and thrombus lysis is more active in ACS patients comparing to controls, that point on a baseline activated hemostasis. Within the ACS group, higher the existing clot in vessel lumen, more active the shift of the balance to anticoagulation and fibrinolysis.